2003
DOI: 10.14214/sf.494
|View full text |Cite
|
Sign up to set email alerts
|

Quality and yield of pulpwood in drained peatland forests: pulpwood properties of Scots pine in stands of first commercial thinnings

Abstract: The inherent structural dynamics of drained peatland forests may result in a great variation in various wood and fi ber properties. We examined variation in fi ber and pulp properties i) among stands, ii) among trees within stands, and iii) within trees in young stands dominated by Scots pine (Pinus sylvestris L.). The stands, selected to cover a maximal range of the potential variation, were all at a stage of development where the fi rst commercial thinnings would be feasible. Differences in the processabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…1) shows the change in the distribution in one selected sapwood growth ring in the longitudinal direction of the stem. As expected (Varhimo et al 2003), the average fiber length first increased from the butt of the stem to an average stem height of 2 m and then decreased towards the stem top with a simultaneous decrease in the narrowness of the distribution.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…1) shows the change in the distribution in one selected sapwood growth ring in the longitudinal direction of the stem. As expected (Varhimo et al 2003), the average fiber length first increased from the butt of the stem to an average stem height of 2 m and then decreased towards the stem top with a simultaneous decrease in the narrowness of the distribution.…”
Section: Resultssupporting
confidence: 82%
“…0.469 (R 2 = 0.974). Varhimo et al (2003) have reported that the variation in pulp yield within trees contributes about two-thirds of the total variation, the remaining one-third owing to the variation between trees. 6 0,8 1,0 1,2 1,4 1,6 1,8 2,0 2,2 2,4 2,6 2,8 3,0 3,2 Fiber length (mm) Relative height of stem (%) Fig.…”
Section: Variation In Fiber Length Within Stemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments are described in detail in Varhimo et al (2003). In both experiments, two unthinned control plots and two heavily thinned plots, adjusted according to the Finnish guidelines for forestry practice (Hyvän metsänhoidon suositukset, 2006), were sampled.…”
Section: Thinning Experiments On Drained Peatland (Dataset Iv)mentioning
confidence: 99%
“…The study was part of a project called "Quality and Yield of Pulpwood in Drained Peatland Forests", which was aimed at quantifying the variation in wood, fibre and pulp properties (Varhimo et al 2003, Rissanen 2003 and yield in peatland stands, and at evaluating the relevance of the current guidelines for silviculture on drained peatland sites regarding their production potential and/or the quality of wood produced.…”
Section: Introductionmentioning
confidence: 99%